Analisis Pengelolaan Soft Skill Berorientasi Kerja Jurusan Pariwisata Fakultas Sastra dan Budaya Universitas Negeri Gorontalo - Hadijah Kader (Peneliti.net, 2021)
This study aims to obtain an overview of the soft skills mastery of students majoring in tourism, Gorontalo State University and to get an overview of the types of soft skills needed by workers in the tourism sector. The data collection techniques in this study used observation, interviews, documentation and questionnaires. The results of this study are that the focus of the research on soft skill mastery can be concluded that the category is sufficient with an average of 70.62, the type of soft skill intrapersonal skill is sufficient with an average of 63.86, the type of soft skill interpersonal skill is in the sufficient category with an average of 69.55 and communication skill with a high category with an average of 78.45. Soft skills needed in the world of work are intrapersonal skills with an average of 94.25 with a very high category, interpersonal skills have an average of 97.56 with a very high category and communication skills have an average of 98.99 with a very high category. These three skills are needed because they support each other, where a person's ability to manage himself will also be able to manage his relationships with other people, and relationships with other people occur through a good communication process.